Delovno- in socialnopravna vprašanja "prisilne upokojitve" - Bagari, Sara (Delavci in delodajalci, 2021)
The paper analyses labour and social law issues raised in connection with the measure of so-called forced retirement, as regulated by the Act Determining Intervention Measures to Assist in Mitigating the Consequences of the Second Wave of COVID-19 Epidemic (ZIUPOPDVE). It allows employers to terminate an employment contract for employees and civil servants who meet the conditions for acquiring the right to an old-age pension without giving a justified operational reason or without substantiating it. After analysing the provisions on forced retirement, we can conclude that they constitute a violation of international legal norms binding on Slovenia. Furthermore, it remains doubtful whether the measure, in the form and manner adopted, meets all the requirements of the principle of proportionality.
Keywords: age discrimination; delovno pravo; diskriminacija na podlagi starosti; forced retirement; intervention measures; interventni ukrepi; labour law; mandatory retirement; obvezna upokojitev; pravo socialne varnosti; prisilna upokojitev; social security law